Nível de atividade física e percepção do ambiente em idosos de Santa Maria - RS - Barros, Temístocles Vicente Pereira (2016)
The aging process is multifactorial and universal, and is influenced by behavioral, biological, genetic and social factors. Regular physical activity and increased physical activity levels (PAL) are associated with decreased morbidity and mortality, prevention and treatment of many diseases, as well as better quality of life and well-being perception. The environment is an influential factor in the adoption of a healthy lifestyle, as it influences health status and can mean the difference between subjects` independence and dependence, especially among the elderly. The objective of this research was to analyze PAL and the environment perception of the elderly residents of Santa Maria-RS. The study is characterized as descriptive, crosssectional and epidemiological. The research was conducted in the urban area of the city of Santa Maria that has 41 neighborhoods, of which three were selected. The study included individuals aged 60 years or over, residents of the selected neighborhoods and the elderly who presented cognitive decline, lived in long-stay institutions or refused to participate were excluded from the research. The social demographic characteristics were collected through an anamnesis, cognitive screening was done using the Mini-Mental State Examination, PAL was determined by the International Physical Activity Questionnaire (IPAQ) validated for Brazilian elderly and to evaluate the environment perception, the adapted version of the Neighborhood Environment Walkability Scale (NEWS) was used. Analysis of absolute and relative frequencies, chi2 test and bivariate and multivariate logistic regressions were performed. The sample consisted mostly of women (65.4%), predominantly aged between 60 and 69 years (50.6%), married (55.8%), who went to school between 1 and 4 years (37.2 %), do not work (88.5%) have incomes between 0 and 2 minimum wages (62.2%) perceive their health positively (50.6%), non-smokers (86.5%) and insufficiently active (81.4%). It was observed that the prevalence of physical activity in leisure time was less than 30% in the three neighborhoods. The elderly from the three studied neighborhoods did not reach the recommendation of 150 minutes/week, presenting a total average of 63.14 minutes (SD = 115.15) of physical activity. From the 41 environment perception variables that were investigated in relation to the practice of 150 minutes of physical activity during leisure time per week, four had p values <0.20, which were selected for the multiple logistic regression model. The variables presence street market and presence of crosswalks close to home remained in the multiple model. With the first variable the subjects were 3.3 times more likely to be physically active, and for the second one,, 2.7 times more likely to be physically active during leisure time. It was conclude that the prevalence of physically active elderly in the city of Santa Maria is low, and that the environmental variables that most influence the practice of physical activity during leisure time are "presence of street market" and "presence of crosswalks close to home". Neighborhood infrastructure variables showed mostly negative frequency responses, since the elderly reported that such structures do not exist in the vicinity of their homes.